Tricuspid Regurgitation: A Review of Current Interventional Management - Maxwell Ambrosino; Matthew Sangoi; Nasser Monzer; Brett Irving; Paul Fiorilli; Benjamin Khazan; Sheldon Goldberg (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2024)
ABSTRACT Tricuspid regurgitation is a common yet clinically complex problem, traditionally managed with diuretic therapy with no observable mortality benefit. Older studies on surgical intervention observed poor outcomes; however, this clinical reasoning predates current surgical approaches and novel transcatheter technology. The tricuspid apparatus is a complex structure that poses a technical challenge for surgeons and interventional cardiologists. Recent advances in surgical techniques and transcatheter therapy, particularly edge‐to‐edge repair devices, have demonstrated promising results for safety, reduction in tricuspid regurgitation, and improving quality of life. We review the clinical, imaging, and hemodynamic findings that characterize patients who should be considered for intervention, alongside the rapidly evolving approaches to interventional management.